Social critique in scorsese's the age of innocence and madden's ethan frome: filmic adaptations of two novels by Edith Wharton - Linden, Helen Maria (1996)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão